1996
DOI: 10.1021/ic960378r
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies on the Ion-Exchanged Phases of a Porous Titanosilicate, Na2Ti2O3SiO4·2H2O

Abstract: A titanosilicate with the ideal formula, Na2Ti2O3SiO4·2H2O, containing unidimensional channels, was synthesized hydrothermally and converted to the hydrogen form by acid treatment. The hydrogen form was partially ion exchanged by sodium ions to obtain a 50% sodium ion exchanged phase. The crystals of the sodium phase, NaHTi2O3SiO4·2H2O, retain the symmetry and unit cell parameters of the parent disodium compound, space group P42/mcm, a = b = 7.832(1) Å, c = 11.945(2) Å, and Z = 4. The sodium ions are located o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
103
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 8 publications
(15 reference statements)
11
103
0
Order By: Relevance
“…These lattice changes and the estimated higher symmetry space group in Eu 3+ -doped sitinakite suggested a different distribution of Eu 3+ cations included in the pore system when compared with sodium sites in sitinakite. A similar effect was also observed in the hydrogen converted as well as in the K + , Cs + and Sr 2+ exchanged forms of titanium and titano-niobium sitinakite [8,9]. The Rietveld refinement suggested that after K exchange, one cation site is located at the center of cavity while the other site is near the framework [8].…”
Section: Resultssupporting
confidence: 61%
“…These lattice changes and the estimated higher symmetry space group in Eu 3+ -doped sitinakite suggested a different distribution of Eu 3+ cations included in the pore system when compared with sodium sites in sitinakite. A similar effect was also observed in the hydrogen converted as well as in the K + , Cs + and Sr 2+ exchanged forms of titanium and titano-niobium sitinakite [8,9]. The Rietveld refinement suggested that after K exchange, one cation site is located at the center of cavity while the other site is near the framework [8].…”
Section: Resultssupporting
confidence: 61%
“…This IEC value is high and comparable to that found for Na2Ti203SiO4.2H20. 8 The experimental curves showing the dependencies of alkali metal ions uptake by the KTS-H in 0.1M MC1-MOH (M=Li, Na, K, Cs) aqueous solutions are presented in Fig. 2a.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis was performed under considerably soft conditions (under air pressure from 3-5 to 0.3-0.4 mPa and at 130-200 • C for 12-24 hours) in comparison with the well-known method by Poojary et al [2]. Changes in the reaction conditions resulted in the product yield increase from 30 to 250-300 g/l of initial reagents.…”
Section: Synthesis Of Titanium Silicates Namentioning
confidence: 99%
“…The Nb substitution increases sorption capacity towards Cs + ions and decreases Sr 2+ selectivity. This effect is attributed to higher coordination number, an increase in the unit cell volume and change in water / Na + population [2]. Among challenging materials are sodium titanate (NaTi 2 O 5 H), titanium silicates with pharmocosiderite structure, sodium nonatitanate (Na 4 Ti 9 O 20 ·xH 2 O), and heteropolymeta-…”
Section: Introductionmentioning
confidence: 99%